Plastic Surgery - Mast, Bruce A. (Thieme Medical Publishers, Incorporated, 2020)
An informative, go-to guide on common plastic surgery principles and practices Plastic Surgery: A Practical Guide to Operative Care by Bruce Mast fills the gap between existing pocket handbooks and encyclopedic library shelf editions. The book is geared towards plastic surgeons early in their careers. The focus is on commonly encountered conditions and is not intended to be an all-inclusive resource. All the surgical chapters are uniformly organized, with discussion of goals and objectives, patient presentation, surgery preparation, treatment, postoperative care, outcomes, and questions. The b.